ASOSIASI FUNGI MIKORIZA ARBUSKULA (FMA) PADA TANAMAN GAHARU AQUILARIA SPP DI DESA LAMAN SATONG KABUPATEN KETAPANG - Huda, Nurul; Muin, Abdurani; rizal, Fah (Universitas Tanjungpura, 2016)
The aim of this study was to determine Genus and association of arbuscular Mycorrhizal fungi (AMF) on the Aquilaria SPP in Laman Satong Village Ketapang Regency. The result of spores observation based on soil samples which taken in the rhizosphere of Aquilaria SPP founded that of spores in 100 g soil is about 340 spores ofsoilGigaspora SP1, 1238 spores of Glomus SP1, 1334 Glomus SP2, 459 spores of Glomus SP3, 442 Glomus SP 4. The infection of AMF in the root of Aquilaria SPP showed that low level until high level of infection is on plants in 1 until to 3 years, while the infection in 5 years plants is low. The conclusions from the observation result about spores and infection of the roots showed Aquilaria SPP associated with AMF and the infection observation in the root of Aquilaria SPP showed rates of infection getting diminishing with ages Aquilaria SPP. Keyword : Arbuscular mycorrhizal fungi, Aquilaria SPP., Association.